Bias detected? An examination of criminal history using the OYAS-DIS for girls and black youth - Miller, William T. (Journal of ethnicity in criminal justice, 2021)
Black youth and girls are at an increased risk of formal involvement in the juvenile justice system. These differential experiences have the potential to harm the validity of the criminal history measures on juvenile risk assessments. The present study examines the incremental validity of the criminal history items on the Ohio Youth Assessment System-Disposition Tool in a sample of 3,591 youth across gender and race. Results indicated that the criminal history items significantly contributed to the predictive validity of the tool for White boys, but this was not the case for Black boys, Black girls, or White girls. Future risk assessments should consider modifying or omitting these items, as they neither predict recidivism nor inform treatment for various youth.